Caracterização histológica e vitrificação de tecido somático de catetos (Pecari tajacu Linnaeus, 1758) - Borges, Alana Azevedo (Universidade Federal Rural do Semi-Árido, 2016)
The cryopreservation of somatic tissue derived from collared peccaries represents an interesting step in the obtainment and conservation of cells for nuclear transfer (cloning). In this sense, tissue vitrification protocols need to be optimized to ensure maximum preservation of viable cell characteristics. Therefore, the aims of this study were to characterize histologically the peripheral auricular integumentary system (Stage 1) and evaluate different cryoprotectants in the solid-surface vitrification of somatic tissue of collared peccaries (Stage 2). Thun, ear fragments (9.0 mm3) were collected of sixteen animals derived from the Multiplication Center of Wild Animals (CEMAS/UFERSA). In the first stage, tissue samples were evaluated for the characterization of layers, its components and proliferative activity. For the second stage, tissue fragments were cryopreserved by solidsurface vitrification using Dulbecco modified minimum essential medium supplemented with 10% fetal bovine serum and different cryoprotectants and concentrations [dimethylsulfoxide (DMSO, 3.0 M), ethylene glycol (EG; 3.0 M) and association DMSO/EG (1.5 M; 1.5 M) in the absence and presence of sucrose (0.25M)]. After two weeks, warmed and non-vitrified (control) fragments were analyzed using histological techniques. Thus, for both steps, tissue samples were evaluated using hematoxylin-eosin and Gomori Trichrome, quantification of regions argyrophilic nucleolar organizer (AgNORs) and viability by MTT assay (3-[4,5- dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide). Also, in the first stage, fragments were analyzed by transmission electronic microscopy. Thus, in the first stage, sizes of 104.2 μm and 222.6 μm were observed in the epidermis and dermis, with a volumetric ratio of 36.6% and 58.7%, respectively. Moreover, in the epidermis were evidenced the basal layer (22.5 μm), intermediate (53.5 μm) and cornea (28.2 μm), with mean values of 65.3 epithelial cells, 43.4 melanocytes and 14.8 perinuclear halos. Already the dermis has 127 fibroblasts with 2.5 AgNORs by nucleolus. Additionally, the metabolic activity was 0.243. In the second stage, the 3.0 M EG with sucrose was able to maintain normal tissue characteristics compared with non-vitrified (control), especially for the volumetric ratio of epidermis (61.2 vs. 58.7) and dermis (34.5 vs. 36.6), number of fibroblast (90.3 vs. 127.0), and AgNOR ratio (0.09 vs. 0.17), respectively. In conclusion, the peripheral auricular integumentary system derived from collared peccaries possessed some variations compared to other mammals, as the number of layers and thickness of the epidermis, number of epithelial cells, melanocytes and proliferative parameters. Moreover, 3.0 M EG with 0.25 M sucrose resulted in a better cryoprotectant composition in the vitritification for somatic tissue of collared peccaries
Histological characterization and vitrification of somatic tissue derived from collared peccaries (Pecari tajacu Linnaeus, 1758)
Keywords: Animais silvestres; Tecido somático; crioprotetor; Wild animals; Somatic tissue; Cryoprotectant; CIENCIAS AGRARIAS::MEDICINA VETERINARIA